2014
DOI: 10.5539/gjhs.v6n4p136
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Healthy Built Environment for Diabetic Patients: The Case Study of the Eastern Province of the Kingdom of Saudi Arabia

Abstract: Many studies worldwide have demonstrated the negative impact of an unhealthy built environment on citizens. In the case of diabetes, studies have concentrated on the environmental impact and accessibility issues of a place i.e. the home and neighborhood, whereas few studies have addressed the comfort of the type and spatial arrangement of a household and linked it with the prevalence of diabetes. Also, little research has tackled the place’s impact on diabetic patients and their views concerning their environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…A review study [43] indicated that participants were more conscious of certain diet and lifestyle habits after the intervention, despite not having used the app because of the information they received during the assessments and questionnaires. In terms of PA improvements, the lack of significant differences was not unexpected for 2 main reasons: first, a meta-analysis of weight-loss apps showed no significant changes in PA [12], and second, three-quarters of Saudi women are characterized as insufficiently active [44], ranking as the least physically active worldwide. Causes for the lack of PA in the KSA include an absence of locations designed for general PA such as sidewalks or green spaces and very limited options for female-oriented PA; only high-cost gyms or sports clubs exist which means that normal daily walking or aerobic movement is not a common activity for either gender [45].…”
Section: Discussionmentioning
confidence: 99%
“…A review study [43] indicated that participants were more conscious of certain diet and lifestyle habits after the intervention, despite not having used the app because of the information they received during the assessments and questionnaires. In terms of PA improvements, the lack of significant differences was not unexpected for 2 main reasons: first, a meta-analysis of weight-loss apps showed no significant changes in PA [12], and second, three-quarters of Saudi women are characterized as insufficiently active [44], ranking as the least physically active worldwide. Causes for the lack of PA in the KSA include an absence of locations designed for general PA such as sidewalks or green spaces and very limited options for female-oriented PA; only high-cost gyms or sports clubs exist which means that normal daily walking or aerobic movement is not a common activity for either gender [45].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the trend of increasing obesity seems to play a prominent part in the rising incidence and changing phenotype of T1D among adolescents and children[7]. Some lifestyle changes and precautions can be incorporated to deter the development of DD for those with and without DM[12,18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…The association between physical inactivity as a risk factor for T2D was assessed in many studies ( Alqurashi et al, 2011 ; Al-Quwaidhi, Critchley, Flaherty, & Pearce, 2013 ; Amin et al, 2014 ; Hu, 2011 ; Qi et al, 2008 ; Midhet et al, 2010a ; Temelkova-Kurktschiev & Stefanov, 2012 ). Unfortunately, lack of physical activity is common among the Saudi population ( Al-Nozha et al, 2007 ; Amin et al, 2014 ; Amin, Al Khoudair, Al Harbi, & Al Ali, 2012 ; Midhet et al, 2010a ; Sidawi et al, 2014 ). For example, AlQuaiz and Tayel (2009) conducted a cross-sectional study on 450 Saudi participants at King Khalid University Hospital (KKUH) in Riyadh city and reported the prevalence of physical inactivity among the participants was 82%.…”
Section: Findings Of the Literature Reviewmentioning
confidence: 99%
“…Certain dietary patterns are homegrown in Saudi Arabia including the consumption of dates, desserts, and meat over rice dishes which contains a high content of fat and carbohydrates ( Al-Khudairy et al, 2014 ; Midhet et al, 2010b ). Additionally, Sidawi et al (2014) reported a quarter of Saudis did not consume the recommended healthy food such as fruits and vegetables, and also quarter of them consumed a lot of unhealthy foods and drinks including French fries, donuts, and energy drinks. In addition to unhealthy diet, smoking is also a risk factor for T2D.…”
Section: Findings Of the Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation